Knowledge and attitudes on hiv transmission in students from a medical school in perú (1999)
A study was carried out in order to determine knowledge and attitudes regarding the transmission of the human immune deficiency virus HIV- among fourth year medical students that were on the epidemiology course at the School of Medicine, Universidad Nacional Mayor de San Marcos in Lima. A questionnaire survey was applied to 204 students with 10 knowledge questions and 05 attitude questions regarding HIV transmission. 91,6 % of the answers on knowledge and 77% of those in attitudes were correct. 46 % of the students indicated that blood donors could transmit HIV; 10 % said that HIV infection could be transmitted via mosquitoes. As for the attitudes, 22% of those surveyed indicated that they would commit suicide if they were HIV infected. The attitude towards suicide was moderately associated with the male sex (OR=2.36). Therefore, most of the students have correct knowledge regarding HIV transmission and a lesser percentage of students, though also important, assumes incorrect attitudes.